2015
DOI: 10.2147/ndt.s79108
|View full text |Cite
|
Sign up to set email alerts
|

Prefronto–cerebellar transcranial direct current stimulation improves visuospatial memory, executive functions, and neurological soft signs in patients with euthymic bipolar disorder

Abstract: ObjectiveThe aim of the study was to improve neuropsychological functioning of euthymic patients with bipolar disorder (BD) using transcranial direct current stimulation (tDCS) applied to cerebellar and prefrontal cortices.MethodsTwenty-five BD outpatients underwent prefrontal (anodal) and cerebellar (cathodal) tDCS for 3 consecutive weeks. All participants were assessed through the Rey Complex Figure Test delay and copy and the Neurological Examination Scale at baseline and after therapy with tDCS.ResultsAfte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…In general, anodal stimulation is believed to enhance motor and cognitive functions, whereas cathodal stimulation typically inhibits functioning. However, in several studies, cathodal stimulation was associated with a neurobehavioral effect in agreement with an enhanced function of the cerebellar cortex (Galea et al, 2011 ; Ferrucci et al, 2012 ; Pope and Miall, 2012 ; Shah et al, 2013 ; Bersani et al, 2015 ; Bocci et al, 2015 ; Bradnam et al, 2015 ; Minichino et al, 2015 ; Panouillères et al, 2015b ). On the other hand some studies have shown that anodal stimulation may impair cerebellar function (Ferrucci et al, 2008 ; Foerster et al, 2013 ; Dutta et al, 2014 ; Macher et al, 2014 ; Bocci et al, 2015 ; Doeltgen et al, 2015 ; Panouillères et al, 2015b ; Chothia et al, 2016 ).…”
Section: Technical Issuesmentioning
confidence: 67%
See 1 more Smart Citation
“…In general, anodal stimulation is believed to enhance motor and cognitive functions, whereas cathodal stimulation typically inhibits functioning. However, in several studies, cathodal stimulation was associated with a neurobehavioral effect in agreement with an enhanced function of the cerebellar cortex (Galea et al, 2011 ; Ferrucci et al, 2012 ; Pope and Miall, 2012 ; Shah et al, 2013 ; Bersani et al, 2015 ; Bocci et al, 2015 ; Bradnam et al, 2015 ; Minichino et al, 2015 ; Panouillères et al, 2015b ). On the other hand some studies have shown that anodal stimulation may impair cerebellar function (Ferrucci et al, 2008 ; Foerster et al, 2013 ; Dutta et al, 2014 ; Macher et al, 2014 ; Bocci et al, 2015 ; Doeltgen et al, 2015 ; Panouillères et al, 2015b ; Chothia et al, 2016 ).…”
Section: Technical Issuesmentioning
confidence: 67%
“…The few studies based on multiple sessions are clinical studies. Most of these studies used multiple 5-day interventions (1–4 weeks) and administered one (Gironell et al, 2014 ; Ho et al, 2014 ; Minichino et al, 2015 ; Ferrucci et al, 2016 ) or two stimulation sessions a day (Bation et al, 2016 ). Bradnam et al ( 2014 ), on the other hand, stimulated twice a week for a period of 12 weeks.…”
Section: Technical Issuesmentioning
confidence: 99%
“…In this regard, bilateral M1 combined with PFC stimulation has been successfully applied (Vines et al, 2008; Mordillo-Mateos et al, 2012; Leite et al, 2013; Naros et al, 2016). However, the characterization of the effects associated to concomitant stimulation of different brain regions is nearly absent in the literature (Kaminski et al, 2013; Minichino et al, 2015) due to the low focality inherent to the technique and the inability from traditional tDCS devices to simultaneously control multiple stimulation electrodes. Indeed, there has been some progression in recent years.…”
Section: Considerations On Motor Learning Modulation and New Perspectmentioning
confidence: 99%
“…A recent literature review cites evidence of the physiological role of the cerebellum in maintaining mood as well as its implication in the pathophysiology of bipolar disorder and major depressive disorder. Minichino et al 30 suggested the cerebellum has roles in cognition, mood and behavior 31,32,33 . In their study, they pointed to the role of the cerebellum in modulating emotional processing, providing strong evidence from clinical and electrophysiological studies to support their view.…”
Section: Discussionmentioning
confidence: 99%